Beyond antiplatelets: The role of glycoprotein VI in ischemic stroke. Issue 6 (August 2016) - Induruwa, Isuru; Jung, Stephanie M; Warburton, Elizabeth A
Background: Platelets are essential to physiological hemostasis or pathological thrombus formation. Current antiplatelet agents inhibit platelet aggregation but leave patients at risk of systemic side-effects such as hemorrhage. Newer therapeutic strategies could involve targeting this cascade earlier during platelet adhesion or activation via inhibitory effects on specific glycoproteins, the thrombogenic collagen receptors found on the platelet surface. Aims: Glycoprotein VI (GPVI) is increasingly being recognized as the main platelet-collagen receptor involved in arterial thrombosis. This review summarizes the crucial role GPVI plays in ischemic stroke as well as the current strategies used to attempt to inhibit its activity. Summary of review: In this review, we discuss the normal hemostatic process, and the role GPVI plays at sites of atherosclerotic plaque rupture. We discuss how the unique structure of GPVI allows for its interaction with collagen and creates downstream signaling that leads to thrombus formation. We summarize the current strategies used to inhibit GPVI activity and how this could translate to a clinically viable entity that may compete with current antiplatelet therapy. Conclusion: From animal models, it is clear that GPVI inhibition leads to an abolished platelet response to collagen and reduced platelet aggregation, culminating in smaller arterial thrombi. There is now an increasing body of evidence that these findings can be translated into the development of a bleeding free pharmacological entity specific to sites of plaque rupture in humans.